Clinical application of metagenomic next-generation sequencing in rapid diagnosis and prognostic assessment of herpes simplex encephalitis - Tang, Jin; Li, Ping; Xu, Haoming; Han, Jingzhe (Frontiers in Microbiology, 2025)
PurposeHerpes simplex encephalitis (HSE) ranks among the most common causes of severe viral encephalitis. It leads to meningitis or encephalitis, with patients frequently encountering adverse outcomes. In this study, we utilized metagenomic next-generation sequencing (mNGS) to rapidly and accurately detect and identify the HSV pathogen directly from cerebrospinal fluid (CSF) samples, aiming to achieve a definitive diagnosis for encephalitis patients.MethodsFrom 2018 to 2023, we prospectively identified and enrolled 28 patients diagnosed with HSE at Hengshui People’s Hospital. CSF samples were subjected to mNGS to facilitate the diagnosis and characterization of HSE in this cohort. We compiled the clinical characteristics, supplementary examinations, and outcomes of HSE patients, with prognosis assessed using the Glasgow Outcome Scale (GOS) scores at discharge, 1 month post-discharge, and 3 months thereafter.ResultsIn this cohort of 28 patients, 12 were females and 16 males, with a mean age of 41.82 ± 18.23. HSE manifested with a variety of clinical symptoms, the most prevalent being headaches (67.9%), fever exceeding 38°C (60.7%), and altered consciousness (60.7%). Seizures (42.9%), vomiting (35.7%), and speech deficits (35.7%) were frequently observed, with a minority of patients displaying personality changes (28.6%). CSF analysis revealed pleocytosis and a mild increase in protein levels. Magnetic resonance imaging (MRI) abnormalities (28.6%) were primarily confined to the frontal and temporal lobes as well as limbic regions, with no indications of cerebral hemorrhage. Half of the patients exhibited Electroencephalogram (EEG) changes suggestive of encephalitis. HSE was confirmed through mNGS analysis of CSF within 3 days of admission. All patients received empirical treatment with ganciclovir, with 46.4% undergoing hormonotherapy and 32.1% receiving immunoglobulin therapy. At the three-month follow-up, 32.1% had GOS scores <5.ConclusionHSE often presents with nonspecific signs of encephalitis, and it’s not easy for traditional CNS examinations to confirm the diagnosis. mNGS serves as a cutting-edge diagnostic tool for the rapid and precise identification of HSE, facilitating timely clinical diagnosis and intervention to prevent the progression of the disease.